What Are the Peripheral Blood Determinants for Increased Osteoclast Formation in the Various Inflammatory Diseases Associated With Bone Loss? - de Vries, Teun J.; el Bakkali, Ismail; Kamradt, Thomas; Schett, Georg; Jansen, Ineke D. C.; D'Amelio, Patrizia (Frontiers in Immunology, 2019)
Local priming of osteoclast precursors (OCp) has long been considered the main and obvious pathway that takes place in the human body, where local bone lining cells and RANKL-expressing osteocytes may facilitate the differentiation of OCp. However, priming of OCp away from bone, such as in inflammatory tissues, as revealed in peripheral blood, may represent a second pathway, particularly relevant in individuals who suffer from systemic bone loss such as prevalent in inflammatory diseases. In this review, we used a systematic approach to review the literature on osteoclast formation in peripheral blood in patients with inflammatory diseases associated with bone loss. Only studies that compared inflammatory (bone) disease with healthy controls in the same study were included. Using this core collection, it becomes clear that experimental osteoclastogenesis using peripheral blood from patients with bone loss diseases in prevalent diseases such as rheumatoid arthritis, osteoporosis, periodontitis and cancer-related osteopenia unequivocally point towards an intrinsically increased osteoclast formation and activation. In particular, such increased osteoclastogenesis already takes place without the addition of the classical osteoclastogenesis cytokines M-CSF and RANKL in vitro. We show that T-cells and monocytes as OCp are the minimal demands for such unstimulated osteoclast formation. In search for common and disease-specific denominators of the diseases with inflammation-driven bone loss, we demonstrate that altered T-cell activity and a different composition - such as the CD14+CD16+ versus CD14+CD16- monocytes - and priming of OCp as seen in peripheral blood play a role in increased osteoclast formation and activity. The putative common denominators, skewness of monocyte subtypes, T-lymphocytes and the contribution of inflammatory cytokines such as TNF-α and M-CSF that are released in osteoclast cultures or that are present in peripheral blood are discussed.